Methadone use for acute opioid withdrawal in Tshwane shelters during the COVID-19 lockdown - Jo-Marie A. Siemens; Urvisha Bhoora; Michelle Janse van Rensburg (South African Family Practice)
Background: Temporary shelters were established for street-based people during the national level 5 coronavirus disease 2019 (COVID-19) lockdown. However, street-based substance users’ need to access substances was not addressed, resulting in large numbers of people experiencing withdrawal. The Community Oriented Substance Use Programme (COSUP) in Tshwane provided methadone to manage opioid withdrawal.